2018
DOI: 10.3389/fpsyg.2018.00493
|View full text |Cite
|
Sign up to set email alerts
|

An Eye Movement Desensitization and Reprocessing (EMDR) Group Intervention for Syrian Refugees With Post-traumatic Stress Symptoms: Results of a Randomized Controlled Trial

Abstract: The number of refugees has increased significantly over the past few years. PTSD and depression are among the most common mental health problems among refugees. Eye Movement Desensitization and Reprocessing (EMDR), an effective treatment for PTSD, is usually administered individually. The availability of mental health resources would be greatly enhanced when EMDR can be delivered to groups. The EMDR G-TEP is a group protocol based on Early EMDR intervention protocols. There is clinical evidence and one field s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 32 publications
2
61
0
Order By: Relevance
“…All 14 included trials with adults were published in peer‐reviewed journals (Table 2). Furthermore, all but two (Shaw, Ward, Pillai, & Hinton, 2018; Yurtsever et al, 2018) applied an individual intervention setting. Multiple comparisons were included from Stenmark, Catani, Neuner, Elbert, and Holen (2013), who reported data for refugees and asylum seekers separately, and from Neuner, Schauer, Klaschik, Karunakara, and Elbert (2004), who included three trial arms.…”
Section: Resultsmentioning
confidence: 99%
“…All 14 included trials with adults were published in peer‐reviewed journals (Table 2). Furthermore, all but two (Shaw, Ward, Pillai, & Hinton, 2018; Yurtsever et al, 2018) applied an individual intervention setting. Multiple comparisons were included from Stenmark, Catani, Neuner, Elbert, and Holen (2013), who reported data for refugees and asylum seekers separately, and from Neuner, Schauer, Klaschik, Karunakara, and Elbert (2004), who included three trial arms.…”
Section: Resultsmentioning
confidence: 99%
“…We included 116 studies (115 papers) in the systematic review. Of these, 50 were conducted in hospital settings , 24 were delivered in a community setting , seven were delivered in military clinics for veterans or active military personnel [103][104][105][106][107][108][109], five were conducted in refugee camps [110][111][112][113][114], four used remote delivery via web-based or telephone platforms [115][116][117][118], four were conducted in specialist trauma clinics [119][120][121][122], two were delivered in home settings [123,124], and two were delivered in primary care clinics [125,126]; clinical setting was not reported in 17 studies [127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The same proportion of people develop posttraumatic stress disorder (PTSD) a few months later, and there is some overlap of the two groups suggesting some kind of connection; however, this relationship has not been proved yet. Some studies have concluded that the two phenomena are independent of each other, while others consider untreated acute stress disorder as the main cause of PTSD [ 4 ]. Some authors argue that their research has found a link between acute stress disorder and completed suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays it is a widely used approach in the treatment of PTSD and other mental disorders accompanying psychological traumas [ 8 ]. One part of our intervention was carried out along the EMDR protocol for acute stress disorder [ 4 , 9 ].…”
Section: Introductionmentioning
confidence: 99%